The elaboration in two stages of the painting Meleager and Atalanta by Jacob Jordaens at the Prado. Technical considerations - Alejandro Vergara; Maite Jover; María Dolores Gayo; Laura Alba (Boletín del Museo del Prado)
Based on appearance alone, scholars have long noticed that Jordaens’s painting Meleager and Atalanta at the Prado is painted in two different styles, one corresponding to each half. The present article presents the findings of a technical study of the painting undertaken at the Prado. The study of the weave and thread count of the two canvases that make up the support of the painting, the study of the painting with infrared reflectography and X-radiography, and the analysis of some of the pigments used in the painting reveal important differences in the materials used in the two halves of the painting.